Stabilizing the Oxygen Lattice and Reversible Oxygen Redox Chemistry through Structural Dimensionality in Lithium‐Rich Cathode Oxides. Issue 13 (19th February 2019) - Zhao, Enyue; Li, Qinghao; Meng, Fanqi; Liu, Jue; Wang, Junyang; He, Lunhua; Jiang, Zheng; Zhang, Qinghua; Yu, Xiqian; Gu, Lin; Yang, Wanli; Li, Hong; et al.
Abstract: Lattice‐oxygen redox (l‐OR) has become an essential companion to the traditional transition‐metal (TM) redox charge compensation to achieve high capacity in Li‐rich cathode oxides. However, the understanding of l‐OR chemistry remains elusive, and a critical question is the structural effect on the stability of l‐OR reactions. Herein, the coupling between l‐OR and structure dimensionality is studied. We reveal that the evolution of the oxygen‐lattice structure upon l‐OR in Li‐rich TM oxides which have a three‐dimensional (3D)‐disordered cation framework is relatively stable, which is in direct contrast to the clearly distorted oxygen‐lattice framework in Li‐rich oxides which have a two‐dimensional (2D)/3D‐ordered cation structure. Our results highlight the role of structure dimensionality in stabilizing the oxygen lattice in reversible l‐OR, which broadens the horizon for designing high‐energy‐density Li‐rich cathode oxides with stable l‐OR chemistry. Abstract : Stabilized by disorder : A stable oxygen‐lattice structure accompanying lattice‐oxygen redox reactions was found in Li‐rich oxide materials used for cathodes. The 3D‐disordered cation framework was identified through the neutron pair distribution function and atomic‐resolution STEM microscopy. The stabilization is attributed to the random spatial distribution of the unhybridized O 2p orbitals in the 3D disordered structure.